2016
DOI: 10.1186/s12974-016-0725-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of nicotine on interleukin 1β activated human astrocytes and the role of cyclooxygenase 2 in the underlying mechanism

Abstract: BackgroundThe cholinergic anti-inflammatory pathway (CAP) primarily functions through acetylcholine (ACh)-alpha7 nicotinic acetylcholine receptor (α7nAChR) interaction on macrophages to control peripheral inflammation. Interestingly, ACh can also bind α7nAChRs on microglia resulting in neuroprotective effects. However, ACh effects on astrocytes remain elusive. Here, we investigated the effects of nicotine, an ACh receptor agonist, on the cytokine and cholinesterase production of immunocompetent human astrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…In the human 3D EpiAirway tissue model, we found that nicotine significantly downregulated IL‐6 secretion by tissues from healthy subjects, while it increased by tissues from COPD subjects. This is in line with nicotine‐mediated inhibition of IL‐6 production in human brain astrocytes in a dose‐dependent manner . PG with or without nicotine induced significant IL‐8 release by both healthy and COPD donors compared to untreated controls, while no changes in PGE 2 in any of the groups were observed.…”
Section: Discussionsupporting
confidence: 83%
“…In the human 3D EpiAirway tissue model, we found that nicotine significantly downregulated IL‐6 secretion by tissues from healthy subjects, while it increased by tissues from COPD subjects. This is in line with nicotine‐mediated inhibition of IL‐6 production in human brain astrocytes in a dose‐dependent manner . PG with or without nicotine induced significant IL‐8 release by both healthy and COPD donors compared to untreated controls, while no changes in PGE 2 in any of the groups were observed.…”
Section: Discussionsupporting
confidence: 83%
“…Astrocytes have functional nicotinic and muscarinic receptors and (controversially) may express butyrylcholinesterase ( Bche/ BuChE) and Ache . Levels of expression and catalytic function appear to vary depending on the stage of development/age and species investigated (Anderson et al, ; Elhusseiny, Cohen, Olivier, Stanimirovic, & Hamel, ; Pabst et al, ; Revathikumar et al, ; Teaktong et al, ; Thullbery, Cox, Schule, Thompson, & George, ). In AD pathology, the number of glial fibrillary acidic protein (GFAP) immunopositive astrocytes in the hippocampus and cortex with nicotinic receptor subtype α7 (α7 nAChR )‐immunoreactivity is increased from 40 –100% in sporadic AD and 50–60% in Swedish amyloid precursor protein (APPswe) 670/671 AD cases, compared to less than 50% in non‐symptomatic patient controls (Teaktong et al, ; Yu, Guan, Bogdanovic, & Nordberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Choline receptor stimulation via AChEIs or nicotine agonists can reduce many pro‐inflammatory signals (Tabet, )—making them an appealing target. When activated by IL‐1β, cultured fetal human astrocytes up‐regulated many pro‐inflammatory cytokines (Revathikumar et al, ). Pretreating cultures with nicotine prior to IL‐1β stimulation leads to a reduction in IL‐6, TNF‐α, IL‐1β, IL‐8, and IL‐13 production.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations